The great epochs of European art [videorecording (DVD)] : the art of the ancient Greeks & the art of the Romans - Imhof, Gabriele (Kultur, 2010)
The Art of the Ancient Greeks traces the development of the portrayal of man in Greek art from the early Archaic kouros and kore up to the Classical statues of youths and Hellenistic statues. The Art of the Romans shows the daring, innovative, functional buildings constructed by Roman engineers and architects and their tremendous theatres, thermae and circus buildings.